Locomotief = Loco-krant = GOC-krant. - Gespreks- en Onthaalcentrum (GOC) Antwerpen (Antwerpen : GOC, 1979)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Dambruggestraat 204, 2060 Antwerpen
Vanaf (1980) okt : Loco-krant ; vanaf (1981) nov : GOC-krant
Nederlands
Periodiek